Analisis Sebaran Lahan Kritis Kawasan Hutan Pada Daerah Aliran Sungai (DAS) Pengabuan - Agus Kurniawan Mastur; Eva Achmad; Joko Asmoro Hadi (Universitas Batanghari Jambi, 2021)
Land use that is not based on its capacity will has impact on land quality decreasing. This will lead to the emerging of critical land. This study aimed to analyze the critical level of forest area in the Pengabuan watershed. Critical land analysis was based on the Regulation of the Director General of Watershed Management and Social Forestry Number P.4/V-SET/2013. There were 4 parameters used, namely: land cover, erosion hazard level, slope and management aspects. Land cover was the main parameter in determining critical land because it had the largest weight. Geographic Information System (GIS) and remote sensing technique were used in data processing and analyzing in order to determine the critical level of land. The results showed that 50.58% of the land in the Pengabuan watershed forest area was classified as moderately critical (95,030.7 ha). Land with potentially critical criteria covering an area of 17,804 ha (75.19%) dominated forest areas within protected areas. Approximately 2.71% (4,457.6 ha) of the forest area with open land cover from forest areas outside protected areas was categorised as higly critical land.